Inheritance of resistance to the deforming pepper mosaic virus, pepdmv, in capsicum (2009)
With the aim to determine the mode of inheritance in three resistant materials, crosses were performed towards three susceptible lines. We followed the backcrossing method used by Warner (1952), based on the mathematical model of Fisher Immer and tedin (1932), described in detail by Mater (1949) and Jenkins (1982, 1984). In this method the genetic variance is partitioned into three components: additive, dominant and epistatic. The backcross method includes the two parents, the F1 hybrid, and the self-pollination of the F1 to form the F2 population, and the backcrosses to both parents. The populations were evaluated for resistance to the pepper mosaic virusPepDMV in greenhouse conditions. The results showed that the model additive-dominant explained the resistance in the hybrids formed between resistant and susceptible material. The genes with heritable action transmit to their offspring the resistance effect. The presence of viral resistance is given by the presence of resistant parents.